Challenges of combining cytotoxic chemotherapy and tyrosine kinase inhibitors. (January 2015) - Chu, Michael P; L Damaraju, Vijaya; Sawyer, Michael B
Single-agent tyrosine kinase inhibitors (TKIs) have significantly improved patient outcomes across multiple tumor subtypes. However, TKI therapy is rarely curative. Early optimism of combining TKIs with cytotoxic chemotherapy failed to produce substantial results in numerous randomized studies. This article highlights potential missteps and improvements in combination therapy thus far, while shedding light on potential improvements for future combinations.